2011
DOI: 10.1177/1545109711399660
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Sonographic Assessments and Clinical Questionnaire in the Diagnosis of HIV-Associated Lipodystrophy

Abstract: The study evaluated the use of sonographic measurements as an alternative to assessments based on clinical or other imaging techniques for the diagnosis of body-fat abnormalities. The study enrolled 179 HIV-infected patients, 81 (45.3%) of them diagnosed as lipodystrophy (LD)-positive based on a clinical standard questionnaire. Association between clinical LD and sonographic measurements of face, right upper limb, subcutaneous abdomen, and visceral compartments was evaluated by multiple logistic regression. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Other problems to be tackled by clinicians and health managers include the progressive, albeit moderate, increase of secondary resistance [ 34 ] and the permanent challenge posed by side effects of different antiretroviral medications, such as lipodystrophy and metabolic syndromes [ 35 ]. However, despite all such caveats and difficulties, the present paper documents a progressive increase of survival times among gay men over successive periods of the decade 1998–2008.…”
Section: Discussionmentioning
confidence: 99%
“…Other problems to be tackled by clinicians and health managers include the progressive, albeit moderate, increase of secondary resistance [ 34 ] and the permanent challenge posed by side effects of different antiretroviral medications, such as lipodystrophy and metabolic syndromes [ 35 ]. However, despite all such caveats and difficulties, the present paper documents a progressive increase of survival times among gay men over successive periods of the decade 1998–2008.…”
Section: Discussionmentioning
confidence: 99%
“…Additional methods, such as MRI, are considered superior in assessment of body composition in the context of HIV, though are less widely available in lower-income settings. Other methods, such as ultrasound, have not been validated for lipodystrophy assessment [ 81 ], and vary considerably on the operator [ 82 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consistent patient improvements observed in the photographs add weight to the validity of the results. Moreover, the efficacy of polyactic acid when compared to other treatments has been shown in several previous comparative studies [22,23,27-29]. A second limitation is the loss of patients to followup, though data available indicated that those lost had similar demographics and treatment outcomes in the early stages to those retained in the later stage.…”
Section: Discussionmentioning
confidence: 98%
“…Similar studies using generic QoL measures such as the SF-36 have sometimes failed to find significant treatment gains [22], while others have failed to show QoL differences between patients with and without lipodystrophy [4]. On the other hand, studies using the ABCD have reported comparable results [23,24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation